Plant-Mediated Effects on Mosquito Capacity to Transmit Human Malaria. - Domonbabele F D S Hien; Kounbobr R Dabiré; Benjamin Roche; Abdoulaye Diabaté; Rakiswende S Yerbanga; Anna Cohuet; Bienvenue K Yameogo; Louis-Clément Gouagna; Richard J Hopkins; Georges A Ouedraogo; Frédéric Simard; Jean-Bosco Ouedraogo; et al. (PLoS Pathogens)
The ecological context in which mosquitoes and malaria parasites interact has received little attention, compared to the genetic and molecular aspects of malaria transmission. Plant nectar and fruits are important for the nutritional ecology of malaria vectors, but how the natural diversity of plant-derived sugar sources affects mosquito competence for malaria parasites is unclear. To test this, we infected Anopheles coluzzi, an important African malaria vector, with sympatric field isolates of Plasmodium falciparum, using direct membrane feeding assays. Through a series of experiments, we then examined the effects of sugar meals from Thevetia neriifolia and Barleria lupilina cuttings that included flowers, and fruit from Lannea microcarpa and Mangifera indica on parasite and mosquito traits that are key for determining the intensity of malaria transmission. We found that the source of plant sugar meal differentially affected infection prevalence and intensity, the development duration of the parasites, as well as the survival and fecundity of the vector. These effects are likely the result of complex interactions between toxic secondary metabolites and the nutritional quality of the plant sugar source, as well as of host resource availability and parasite growth. Using an epidemiological model, we show that plant sugar source can be a significant driver of malaria transmission dynamics, with some plant species exhibiting either transmission-reducing or -enhancing activities.